Market efficiency and behavioral biases in the WNBA betting market - Rodney Paul; Andrew Weinbach (International Journal of Financial Studies, 2014)
The betting market for the Women's National Basketball Association (WNBA) is a thin financial market, which does not attract much interest from sports bettors. Given these characteristics, it is possible that profitable wagering strategies could exist for informed bettors of the WNBA. Using betting data on the WNBA from 2007 - 2012, we find that simple betting strategies do not earn statistically significant returns. WNBA bettors are like NBA bettors; however, in that they strongly prefer the best teams, particularly when they are on the road. Despite this clear bias, betting against the most popular public wagers is not found to earn statistically significant profits.
Keywords: G14; G10; G02; 330; efficient markets; gambling; behavioral biases